SOCIOLINGUISTIC ANALYSIS OF SOME ANTHROPOMORPHIC METAFORES IN SCIENTIFIC TEXTS (Archive of Conferences, 2020)
The article analyzes the linguistic, sociolinguistic, cognitive-pragmatic features of some anthropomorphic metaphors in scientific texts. In world and Uzbek linguistics, the advantages of studying anthropomorphic metaphors on the basis of scientific texts, anthropomorphic metaphors are analyzed as the main means of increasing the influence of scientific and economic texts